Decoding the Semantic Marvels of the Quran: The Intricate Meanings of 'Home' in Islamic Architecture - Yulianto, Yulianto (SHAHIH: Journal of Islamicate Multidisciplinary, 2023)
This research examines the i’jaz (scientific miracles) of the Quran concerning the semantic field of the word al-baytu within the study of Islamic architecture, a topic that has not been previously explored. The study draws data from Quranic verses containing the term al-baytu and the semantic field of the word al-baytu, such as al-manzilu, al-maskanu, and others. The data collected is then interpreted through the lens of i’jaz (scientific miracles) of the Quran following the terminological framework of the Quranic lexicon. The interpreted results are subsequently analyzed using componential analysis. Based on the results and discussion, it is concluded that the i’jaz (scientific miracles) of the Quran in the semantic field of bayt in the Quran includes terms such as al-maskanu, al-baytu, al-qosru, al-manzilu, ad-dāru, al-qoryatu, and al-madīnatu. Al-maskanurefers to a single dwelling that provides comfort, unlike al-baytu, which also signifies a single dwelling but does not or cannot provide comfort. Al-maskanu is akin to the concept of "home," whereas al-baytu resembles the concept of "house." Al-manzilu serves as a hypernym for the terms al-maskanu and al-baytu, meaning a general place of residence, whether it provides comfort or not. Meanwhile, al-qosru denotes a luxurious residence. Ad-dāru refers to a single house along with its yard. Al-qoryatu is a collection of houses belonging to a community with racial and blood ties. Finally, al-madīnatu is a collection of houses belonging to a society with diverse tribes and races, not bound by blood ties.